PECULIARITIES OF PHYSICAL-CHEMICAL CONDITIONS OF WATER SOLUBLE SALTS CRYSTALLIZATION. - PAPKA, Ye.; NESTEROVSKYI, V.; BOHATYRENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is anoted to the analise and elaborate mathematical apparatus, wich is used for characteristic the process of crystallization of solid tase from solushions.